Development of mobile application of the empower-sustain cardiovascular risk self-management tool with dynamic visualization / Anis Syazwani Abdullah - Abdullah, Anis Syazwani (2018)
The empower sustain cardiovascular risk self-management tool is a healthcare mobile application. It will be used by patient with cardiovascular disease risk. Patient and provider use distinct type of mobile health technology to enhance medical care and well balance administrative works. The easiest way in represent data for better understanding visual presentation is using graph and charts. Using this cardiovascular risk self-management tool mobile application, patient could complete cardiac rehabilitation without problem. Physician could entertain all their patient as they less likely to be occupied. This is from the help of mobile phone application. The public medical facility is not congested anymore. Consequently, doctor is always available in treating and monitoring patient. The data shown is easily being translated. The aim for this development are to study and identify flaws of the existing cardiovascular risk self-management tool. To design and develop sustainable with innovative technology to empower people and could exchange information with primary health care together with dynamic visualization. To evaluate the mobile application through functionality test. This study focusses on developing android mobile application, creating dynamic visualization from intricate data. The platform use is Android Studio, Bootstrap framework, Adobe Dreamweaver, Notepad++ software, PHP, HTML, JavaScript, CSS languages and MySQL for the database. The methodology used are agile method. It consists of requirement, design, development, testing, evaluation and release phase. The coding and database were done step by step. With this tool, patient had awareness and knowledge inn what happen to their body. This also help them achieving treatment target. Thus, complication for cardiovascular risk patient could be prevented. Lastly, this mobile application consists of numerous function that could help patient and doctor. Hence, the problem with barrier attending rehabilitation, shortage care, extra charge and unsightliness of data as stated in the problem statement was solved.